PRODUKSI ALKOHOL DARI SAMPAH RUMAH TANGGA - Nanang Mudjito (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2009)
This research was aimed to produce alcohol from organic solid waste using Saccharomyces cerevisiae. The solid waste was treated in varied sizes and yeast concentrations. The procedure involved size reduction by cutting the solid waste, followed by steaming. The next stage was addition of yeast for fermentation. Size variations were 3 and 10 cm. Each sample was of 2 kg weight. Samples were steamed for 30 and 60 minutes. Yeast was added in different amounts of 0%, 10%, 20%, and 30%. Fermentation was done within 2, 4 and 8 days. The highest alcohol volume of 505 mL was obtained in the reactor, WITH fine solid waste of 3 cm, which had been steamed for 60 minutes, and added by of 30% yeast, with fermentation time of 8 days.